Determination of volatile organic compounds by HS‐GC‐IMS to detect different stages of Aspergillus flavus infection in Xiang Ling walnut. Issue 5 (11th March 2021) - Wang, Shan; Mo, Haizhen; Xu, Dan; Hu, Huiling; Hu, Liangbin; Shuai, Liang; Li, Hongbo
Abstract: The aim of this study was to evaluate the performance of volatile organic compounds (VOCs) for evolution monitoring and early detection of Aspergillus flavus ( A. flavus ) contamination in walnuts. We successfully applied headspace–gas chromatography–ion mobility spectrometry (HS‐GC‐IMS) to evaluate walnut VOC changes caused by A. flavus contamination. A total of 48 VOCs were identified in walnuts contaminated with A. flavus . After identification of VOCs, a heat map and principal component analysis (PCA) highlighted ethyl acetate‐D, 3‐methyl‐2‐butanol, and cyclohexanone as potential biomarkers specific to A. flavus contamination in walnuts. These results provided valid targets for the development of sensors to evaluate the early mold contamination in stored walnuts. Abstract : The aim of this study was to evaluate the performance of volatile organic compounds (VOCs) for evolution monitoring and early detection of Aspergillus flavus ( A. flavus ) contamination in walnuts. These results provided valid targets for the development of sensors to evaluate the early mold contamination in stored walnuts.